Marxist Aesthetics: Exploring Karl Marx And Friedrich Engels’ Perspectives On Art And Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The text extensively discusses Karl Marx and Friedrich Engels’ approach to art and literature in an academic manner. It elaborates on their thoughts by referencing various sources, particularly focusing on Marx’s literary inclinations in detail. It explains Marx and Engels’ understanding of realism, their perspective on art, and the relationship between art and societal transformation, while conveying the fundamental principles of Marxist aesthetics. Additionally, the text delves into how art influences the structure of society and elaborates on the evolution of socialist realism. Therefore, the text provides an in-depth analysis of Karl Marx and Friedrich Engels’ perspectives on art and literature using an academic language.